Alterações ambientais e os riscos de transmissão da Leishmaniose Tegumentar Americana na área de influência da UHE Serra do Facão, Goiás, Brasil - Rodrigues, Elisângela de Azevedo Silva (2011)
The disease Leishmaniasis is transmitted by the bite of bloodsucking female sand flies infected domestic and wild animals. The construction of hydropower plants (HPP), usually cause environmental changes in its area of influence, which can alter cycle of transmission these diseases, producing outbreaks. This work aims to study sand flies caught in the area of influence by UHE Facão Serra, Goias, Brazil, before, during and after filling the reservoir, relating them to environmental changes and climatic seasonality. Six points were selected for capture of sand flies. These points in the period August 2008 to July 2010 were held 72 catches totaling 216 hours of field work, using traps CDC (Center on Disease Control) and Shannon, in which 6,169 sandflies were captured 16 species of the genus Lutzomyia the following species: L. neivai (Pinto, 1926) (93.51%), L. whitmani (ANTUNES; Coutinho, 1939) (2.33%), L. pessoai (COUTINHO, BARRETO, 1940) (2.35%), L. davisi (ROOT, 1934) (1.07%), L. lenti (Mangabeira, 1938) (0.47%), L. termitophila (Martins, HAWK, SILVA, 1964) (0.21%), L. shannoni (Dyar, 1929) (0.15%), L. misionensis (Castro, 1959), (0.11%), L. christenseni (YOUNG, DUNCAN, 1994) (0.10%), L. mamedei (Oliveira, Afonso; DAYS; BRAZIL) (0.10%), L. quinquefer (Dyar, 1929) (0.05%), L. sallesi (Galvão; Coutinho, 1939) (0.08%), L. lutziana (COSTA LIMA, 1932) (0.05%), L. cortellezzii (COSTA LIMA, 1932) (0.03%), L. flaviscutellata (Mangabeira, 1942) (0.02%), L. sordellii (Shannon, Del Ponte, 1927) (0.02). Among the species captured, four have epidemiological importance because they are incriminated in transmission of American cutaneous leishmaniasis (ACL): Lutzomyia neivai, 5741 specimens captured in six points; Lutzomyia pessoai. 103 caught in five points; Lutzomyia whitmani, captured in 144 Lutzomyia flaviscutellata four points and only one specimen taken at one point. L.neivai was the predominant species in catches, and therefore can be considered as the prime suspect in conveying the etiologic agent of ATL in reservoir area of influence of UHE Facão Serra, given the high prevalence of this species in six points studied. The serious risk of transmission ACL in influence area the reservoir of UHE Facão Serra can be described as follows: during fall and winter, driest periods of year when density of phlebotomine is higher, coinciding with the opening of fishing period, in darkest nights of new moon and last quarter, with temperature range above 5 ° C from evening and winds not exceeding 6 km / h. For the effective control of LTA will be necessary to continue performing actions in health surveillance, monitoring environmental change and territorial reorganization now underway in the region with deployment of real estate and tourism related to formation of lake and also monitoring of disease vectors. Still, educational campaigns should be conducted among the local population, that is a permanent resident in areas of greatest risk of transmission, is floating population that frequents area for recreation, especially on weekends and holidays, to prevent disease transmission .